Performance Evaluation of Lightweight Cryptography Hybrid Algorithms for Data Security - Patil, Siddeshwari; Bansode, Rajesh (Karshi Multidisciplinary International Scientific Journal, 2025)
With the rapid expansion of digital communication and data exchange, ensuring data security has become paramount. Traditional cryptographic methods often struggle with balancing security, efficiency, and lightweight implementation for resource-constrained environments. This research focuses on the performance analysis and development of a lightweight cryptographic algorithm for enhanced data security by implementing Simon, Speck, and ChaCha20 individually, as well as in hybrid combinations—Simon-ChaCha20 and Speck-ChaCha20. A key research gap addressed is the need for cryptographic solutions that offer high security while maintaining computational efficiency for diverse data types. The main objective is to evaluate these algorithms based on their avalanche effect, encryption, and decryption performance across different data types, including text, audio, video, and document files. The entire methodology involves implementing and testing the individual and hybrid algorithms, analyzing their avalanche scores for text data, and comparing encryption and decryption times for various file formats. Results of this work indicate that hybrid algorithms achieve a higher avalanche score, demonstrating enhanced security, while also being adaptable for multimedia data encryption. The study’s findings have significant implications for lightweight cryptographic applications in Internet of Things (IoT), embedded systems, and real-time secure communication, offering a robust and efficient encryption approach for modern cybersecurity challenges.